A novel approach to standardised recording of bleeding in a high risk neonatal population. Issue 3 (9th November 2012) - Venkatesh, Vidheya; Curley, Anna; Khan, Rizwan; Clarke, Paul; Watts, Timothy; Josephson, Cassandra; Muthukumar, Priyadarsini; New, Helen; Seeney, Frances; Morris, Scott; Stanworth, Simon
Abstract : Background: Bleeding assessment tools have been developed in other specialties to standardise the recording of bleeding for clinical haemostatic outcomes in transfusion trials, but such tools have not been developed for routine use in neonatology. Aim: The objective of this study was to develop, refine and evaluate a neonatal bleeding assessment tool (NeoBAT) to standardise the clinical recording of bleeding in premature and term neonates in an intensive care setting. Methods: This prospective neonatal international multicentre study included all episodes of bleeding in infants admitted to the intensive/high dependency care nursery over a 2–4-week period. The NeoBAT was developed to record neonatal bleeding episodes. We tested its reliability and reproducibility with duplicate assessments. Results: Duplicate assessments revealed 98% concordance. Bleeding occurred in 25% (37/146) of infants overall and was most common in preterm infants. 11% (16/146) infants had major/severe bleeds, 1% (2/146) moderate and 13% (19/146) minor bleeds. Conclusions: Bleeding is common in premature and term neonates admitted to intensive/high dependency care nurseries. This novel bleeding assessment tool facilitates prospective recording of bleeding events in neonatal intensive care settings and may allow standardised bleeding assessments in this high risk population.